The determination of agreement between Transducer-Like Enhancer split-1 (TLE-1) and Fluorescence In Situ Hybridization (FISH) in synovial sarcoma cases - Salehan, Noraziah (2018)
The emergence of transducer-like enhancer of split 1 (TLE-1) as a new immunohistochemical (IHC) marker for synovial sarcoma (SS) have recently offered an alternative diagnostic strategy to pathologists in differentiating SS from other histologic mimics. Our major aim is to determine the agreement between TLE-1 IHC expression with the translocation X;18 in fluorescence in situ hybridization (FISH) for diagnosing SS. However, due to poor t(X;18) FISH signal, this paper describes troubleshooting plans for FISH analysis that were carried out in determining positive signals for t(X;18). We conducted a cross sectional study using 27 archived formalin-fixed paraffin embedded tissue blocks of synovial sarcoma, which was diagnosed in Hospital Universiti Sains Malaysia from year 1999 to July 2017. Histology assesment was performed to identify SS morphology subtypes. All samples were stained for TLE-1 by immunohistochemistry (IHC) and correlate morphology subtypes. In addition, (FISH) study were performed on formalin-fixed paraffin embedded tissue sections using break-apart SYT probe ,which hybridized to target the breakpoint gene. Troubleshooting for FISH were carried out in obtaining positive t(X;18) signal in SS cells